Synthesis and characterization of mesoporous zinc oxide nanoparticles and evaluation of their biocompatibility in L929 fibroblasts - Zahra Jowkar; Ali Moaddeli; Fereshteh Shafiei; Tara Tadayon; Seyed Ahmadreza Hamidi (Wiley, 2024)
Abstract Objectives This study aimed to synthesize and characterize mesoporous zinc oxide nanoparticles (ZnO NPs) and also to evaluate the cytotoxicity of mesoporous ZnO NPs on L929 mouse fibroblast cell lines using 3‐(4,5‐ dimethylthiazol‐2‐yl)‐2,5‐diphenyl tetrazolium bromide (MTT) assay. Materials and Methods The synthesized mesoporous ZnO NPs were extensively characterized using X‐ray diffraction analysis (XRD), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) analysis, field emission scanning electron microscopy (FESEM), energy dispersive X‐ray spectra (EDAX), Fourier‐transform infrared spectroscopy (FTIR), and dynamic light scattering (DLS). The cytotoxicity of mesoporous ZnO NPs was assessed by MTT assay. The study groups for cytotoxicity assay were normal saline, 0.1% calcined mesoporous ZnO NP solution, 1% calcined mesoporous ZnO NP solution, 0.1% noncalcined mesoporous ZnO NP solution, 1% noncalcined mesoporous ZnO NP solution, 0.1% ZnO NP solution, 1% ZnO NP solution, 2% chlorhexidine, and phosphate‐buffered saline (PBS). The percentages of mean ± standard deviation of viable cells were analyzed. Results Characterization of mesoporous ZnO NPs revealed that all the particles were in a more or less spherical shape with a wide particle size distribution of 70-100 nm. TEM image showed the uniformed and aggregated ZnO NPs with a typical size of 10-15 nm. BET analysis showed a mesoporous structure for the prepared mesoporous ZnO NPs. According to the MTT assay, chlorhexidine had the lowest cell viability percentage. Cell viability percentages of 0.1% mesoporous ZnO NP solutions (calcined and noncalcined) were statistically, significantly higher than 0.1% ZnO NP solution (p < .05). Cell viability percentages of 0.1% calcined and noncalcined mesoporous ZnO NP solutions and 0.1% ZnO NP solution were statistically, significantly higher than the 1% solutions (p < .05). Conclusion Mesoporous ZnO NPs exhibited less cytotoxicity against L929 mouse fibroblast cell lines compared to CHX and ZnO NPs, hence are safe to use.